NASCENT PERIOD ANALYSIS, FACTORS THAT ARE IMPORTANT TO STARTING A BUSINESS, BUSINESS MOTIVATION, AND EFFECTIVENESS OF IMPLEMENTATION OF STUDENT ENTREPRENEURSHIP PROGRAM: CASE STUDY OF BUSINESS START-UP MEMBERS OF HIPMI PT UNIVERSITAS WIDYATAMA - Ongky Suryasyechan P; Febi Cyntia Rinanto; I. Solihin (JURNAL DARMA AGUNG, 2023)
This study aims to find out what the nascent period of Widyatama University students is and what factors they think are important to get out of the nascent period to become a start-up business. This study also aims to determine the motivation of students who are the sample of entrepreneurship research and whether the Student Entrepreneurship Program (PKM) has been running effectively in helping students who are the research samples to become new entrepreneurs. The research method used in this study is the Ex Post facto descriptive method. Ex Post Facto research on new entrepreneurs who became the research sample aims to reveal the factors that they consider important to start a business. They were also asked about the nascent period, motivation for entrepreneurship, the choice of business to run, the amount of business capital needed, and the effectiveness of implementing the PKM program at Widyatama University. The results of the study show: (1) The nascent period of the entrepreneurs of HIPMI PT Widyatama is much shorter than the nascent period of the previous research which reached more than one year. (2) Capital is still considered the most important factor to start a business. (3) Based on the motivation to start a business, most of the research samples can be classified as opportunity-based entrepreneurs. (4) The PKM program run by the government has effectiveness in supporting the formation of entrepreneurs on the Widyatama University campus.